Development of PM2.5 and NO2 models in a LUR framework incorporating satellite remote sensing and air quality model data in Pearl River Delta region, China. (July 2017) - Yang, Xiaofan; Zheng, Yixuan; Geng, Guannan; Liu, Huan; Man, Hanyang; Lv, Zhaofeng; He, Kebin; de Hoogh, Kees
Abstract: High resolution pollution maps are critical to understand the exposure and health effect of local residents to air pollution. Currently, none of the single technologies used to measure or estimate concentrations of pollutants can provide sufficient resolved exposure data. Land use regression (LUR) models were developed to combine ground-based measurements, satellite remote sensing (SRS) and air quality model (AQM), together with geographic and local source related spatial inputs, to generate high resolution pollution maps for both PM2.5 and NO2 in Pearl River Delta (PRD), China. Four sets of LUR models (LUR without SRS or AQM, with SRS only, with AQM only, and with both SRS and AQM), all including local traffic emissions and land use variables, were compared to evaluate the contribution of SRS and AQM data to the performance of LUR models in PRD region. For NO2, the annual model with SRS estimate performed best, explaining 60.5% of the spatial variation. For PM2.5, the annual model with traditional predictor variables without SRS or AQM estimates showed the best performance, explaining 88.4% of the spatial variation. Pollution surfaces at 200 m*200 m resolution were generated according to the best performed models. Graphical abstract: Highlights: Provide high resolution pollution surface for PM2.5 and NO2 in Pearl River Delta. Incorporate remote sensing and air quality model estimates in land use regression. Evaluate performance of traffic emission inventory in land use regression models. Provide essential inputs for exposure and health research. Abstract : This research provided high resolution pollution surface for PM2.5 and NO2 by incorporating remote sensing and air quality model estimates in land use regression.